PENGARUH KOMUNIKASI INTERPERSONAL DAN MOTIVASI EKSTRINSIK TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT TUAH NEGERI KABUPATEN MUSI RAWAS - Supriyanto Supriyanto; Rendi Juliansyah (LPPM UNIVERSITAS BINA INSAN, 2017)
The purpose of the research was to find out how much influence Interpersonal Communication and Extrinsic Motivation had on Employee Performance at the Office of the Tuah Sub-District of Musi Rawas. The population in this study were 37 employees of the Office of the Tuah Sub-District Head Office of Musi Rawas and the number of samples was taken from the entire population. The technique of collecting data uses questionnaires (observation), observation and documentation. The data analysis technique used is the classical assumption test (normality test and linearity test), multiple linear regression, determination coefficient and F. test where the researcher uses the help of IBM SPSS version 20. The regression analysis results obtained the equation: Ý = 7.346 + 0.303X1 + 0.534X2 The results of the regression analysis also obtain the value of the coefficient of determination (R2 = 0.446) or equal to (44.6%). This means (44.6%) variable employee performance is influenced by interpersonal communication and extrinsic motivation. While the remaining 55.4% is influenced by variables other than interpersonal communication and extrinsic motivation, such as discipline, work ethic, and leadership. The conclusion is: Interpersonal communication and extrinsicmotivation significantly influence employee performance at the Office of the Tuah Sub-District Head of Musi Rawas. This is evident from the results of the F test which obtained Fcount = 13,700> F table = 3.26 received at the 5% significance level.